Delineating a typology for co-designing whole farm prototypes under smallholder mixed farming systems in Malawi: Exploring options for sustainable intensification through legume integration in different farm types at Mtunthama Extension Planning Area (EPA) in Malawi - Kamwana, Florence; Chiduwa, Mazvita S.; Groot, Jeroen C.J.; Mabhaudhi, Tafadzwanashe (International Maize and Wheat Improvement Center, 2024)
Smallholder farming in Malawi is characterized by mixed crop-livestock farming, with immense pressure on a degraded natural resource base and limited capacity for smallholders to provide external inputs. These systems can benefit from redesign to achieve sustainable intensification to better meet farmers production, environmental and human objectives. The complexity of smallholder farms, shown by diversity in spatial distribution, resource endowment, production and consumption decisions often hinder the design, targeting, implementation and scaling of agricultural development projects. Understanding farm heterogeneity is crucial for targeting interventions that can potentially improve crop productivity, food security and livelihood sustainability. Famers in Mtunthama EPA primarily cultivate tobacco as their main cash crop, while maize remains the key staple food for household consumption. Additionally, some farmers grow legumes, under limited production, often relying on locally sourced or recycled seed from previous years or passed on from others in the community. A wide range of farm sizes are found in this EPA with a considerable number of farmers having more than 5 acres of land. With respect to agroecological conditions, Central Region has high crop production potential, providing significant opportunities for intensive and diversified farming practices. The larger farm sizes in Mtunthama enable farmers to implement more sustainable and intensive mixed farming systems (MFS), incorporating both crop and livestock production. This study was conducted in Mtunthama Extension Planning Area (EPA), in Kasungu District, Central Region, Malawi, selected as one of the Malawi action sites for the One CGIAR Initiative on Sustainable Intensification of Mixed Farming Systems (SI-MFS). The initiative aims to enhance agricultural productivity and improve livelihoods by enhancing sustainability using several socio-technical innovation bundles (STIBs). These include the introduction of climate-smart practices, improved soil fertility management, and the use of high-yielding crop varieties, all aimed at enhancing food security and resilience to climate change. The effects of these STIBs on farmers’ livelihoods must be reliably monitored and evaluated using robust indicators. The current study consisted of two steps, first summarizing the heterogeneity of farms in Mtunthama EPA by systematically allocating them to homogenous groups with respect to selected structural and functional indicators using statistical methods. A second step consisted of redesigning model farms per farm type, based on evaluation of farm performance and optimizing for production, environmental and profitability using the SI-MFS STIBs, and employing the FarmDESIGN model. Data was collected from focus group discussions (FGDs), and 44 household interviews carried out with smallholder farmers hosting mother trials in the initiative. Principal component analysis (PCA), multiple correspondence analysis (MCA) and cluster analysis were used to analyse quantitative and qualitative data variables and aggregate farms into farm types according to production means, socio-economics and demographics. Four farm types were identified, viz (i) Farm Type I - High resource-endowed (ii)Farm Type II - Medium-high resource-endowed (iii) Farm Type III - Medium-low resource-endowed legume growers, and (iv) Farm Type IV - Low resource-endowed maize growers with no livestock income (resource constrained). Type I farms are characterized by larger land size and higher household income compared to the other farm types. Labor was identified as a major challenge, with high labour cost relevant for type I farms, while household size has more bearing for type II, III and IV farms. The farms types exhibited variable livelihood strategies, and all participated in markets to varying extents. Strengthening market links is therefore imperative for the community. The use of multivariate methods allowed for the identification of the most discriminating variables for farm type delineation and subsequent clustering of farms. This forms the basis for further exploring variability across farm types for the targeting of management interventions for livelihood sustainability. Recommendations include crops rotation, strip cropping, conservation agriculture, access to micro loans facilities, agroforestry and other context-specific practices that address the unique conditions of each farm type to foster more sustainable and productive farming systems. By integrating various MFS activities in central Malawi, the Mtunthama EPA serves as a critical site for demonstrating the potential of sustainable intensification practices. This integration aims to enhance agricultural productivity and sustainability within the region.